Structural and Electronic Investigation of Tetrachalcogenidomolybdate Dianions. Issue 21 (1st June 2018) - Chang, Alison S.; Pintauer, Tomislav; Basu, Partha; Eckenhoff, William T.
Abstract: Four compounds with tetrachalcogenidomolybdate dianions were examined under identical conditions by single crystal X‐ray diffraction and density functional theory (DFT) calculations. Structural comparisons of bond lengths and angles were made looking at effects of counter‐cations and type of chalcogenide (S or O). Ultimately, bond lengths and angles were found to be fairly regular for each anion and in good agreement with computational results, with exceptions likely stemming from close contacts in the crystal packing. A trend of increasing bond lengths was observed with increasing cation size. The most notable structural deviation occurred in [MoO2 S2 ] 2−, where the theoretical structure has a smaller O−Mo‐O angle and a larger S−Mo‐S angle, which was opposite in the crystal structure. This is likely attributed to N−H—S and N−H—O interactions. Both experimental and computational results suggest that uniform charge delocalization in all four structures. The HOMO‐LUMO gap increases significantly with increasing number of oxygen atoms and electronic transitions were determined to be all ligand to metal charge transfer (LMCT). Abstract : Molecular structures of tetrachalcogenidomolybate anions were reported and compared. Changing size and nature of the cation affected crystal packing but Mo−S bonds remained fairly consistent throughout. The electronic structures of several anions were described in detail and predicted spectra compared well with those measured experimentally.